Oxidative Stress in Alzheimer's Disease: In Vitro Therapeutic Effect of Amniotic Fluid Stem Cells Extracellular Vesicles. (24th October 2020) - Gatti, Martina; Zavatti, Manuela; Beretti, Francesca; Giuliani, Daniela; Vandini, Eleonora; Ottani, Alessandra; Bertucci, Emma; Maraldi, Tullia
Abstract : Alzheimer's disease (AD) is characterized by abnormal protein aggregation, deposition of extracellular β -amyloid proteins (A β ), besides an increase of oxidative stress. Amniotic fluid stem cells (AFSCs) should have a therapeutic potential for neurodegenerative disorders, mainly through a paracrine effect mediated by extracellular vesicles (EV). Here, we examined the effect of EV derived from human AFSCs (AFSC-EV) on the disease phenotypes in an AD neuron primary culture. We observed a positive effect of AFSC-EV on neuron morphology, viability, and A β and phospho-Tau levels. This could be due to the apoptotic and autophagic pathway modulation derived from the decrease in oxidative stress. Indeed, reactive oxygen species (ROS) were reduced, while GSH levels were enhanced. This modulation could be ascribed to the presence of ROS regulating enzymes, such as SOD1 present into the AFSC-EV themselves. This study describes the ROS-modulating effects of extracellular vesicles alone, apart from their deriving stem cell, in an AD in vitro model, proposing AFSC-EV as a therapeutic tool to stop the progression of AD.